When Ethics Matters – Interpreting the Ethical Discourse of Small Nature-Based Entrepreneurs - Lahdesmaki, M. (Journal of business ethics, 2005)
This article examines the unique ethical concerns faced by small nature-based entrepreneurs in their everyday business operations. By using qualitative, empirical data, six kinds of business situations were identified to bring about moral consideration for all the entrepreneurs in this study. The business situations identified were the selection of raw material suppliers, reconciling the quality of production and the lack of resources, the pricing process, the content of marketing information, the close relationships to employees and the collaboration with other entrepreneurs. The ethical argumentation used in these business situations was examined in relation to three ethical theories: utilitarian ethics, deontology and virtue-ethics. This article shows that typical for the decision-making of the small nature-based entrepreneurs in an ethical sense is the variety of ethical arguments used and the important role of customers and employees influencing the ethical views of the entrepreneurs.